2018
DOI: 10.1128/aem.02082-17
|View full text |Cite
|
Sign up to set email alerts
|

The Tape Measure Protein Is Involved in the Heat Stability of Lactococcus lactis Phages

Abstract: Virulent lactococcal phages are still a major risk for milk fermentation processes as they may lead to slowdowns and low-quality fermented dairy products, particularly cheeses. Some of the phage control strategies used by the industry rely on heat treatments. Recently, a few phages were found to be highly thermo-resistant. To identify the genetic determinant(s) responsible for the thermal resistance of lactococcal phages, we used the virulent phage CB14 (of the 936 [now ] phage group) to select for phage mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
12
0
2
Order By: Relevance
“…The size of this protein in CB19 is 996 amino acids that is the same size of the other heat-resistant phages SL4, CB13, and CB20, whereas the size of the protein in heat-sensitive, wild-type CB14 is 999. The size of the heat-resistant mutants of CB14 is, however, 959 (81). These data seem to indicate that shorter TMPs are associated with resistance to heat.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The size of this protein in CB19 is 996 amino acids that is the same size of the other heat-resistant phages SL4, CB13, and CB20, whereas the size of the protein in heat-sensitive, wild-type CB14 is 999. The size of the heat-resistant mutants of CB14 is, however, 959 (81). These data seem to indicate that shorter TMPs are associated with resistance to heat.…”
Section: Discussionmentioning
confidence: 83%
“…Lactococcus phage CB19 belongs to a group of phylogenetically related heat-resistant phages that comprises P1532, SL4, CB13, and CB20. These phages show a remarkable resistance to heat and remain infectious after heat treatment at 80°C for 5 min (81). Molecular characterization of heat-resistant mutants of phage CB14, a related phage that infects the same host as CB19, suggests that resistance to heat is due to the amino acid sequence of TMP, a structural protein within the phage tail.…”
Section: Discussionmentioning
confidence: 99%
“…We identified a high proportion of TRs in genes coding for structural proteins, particularly for tail proteins. While it referred to another category of repeats, it was recently demonstrated that the flexibility of an interspersed repeat region in the TMP enabled the virulent Lactococcus phage CB14 to evolve thermal resistance (Geagea et al ., 2017). In addition to the TMP, a large proportion of the TRs was identified in tail fiber proteins (3.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicate that phage Ro145clw is resistant to a pH change from 5.1 to 10.5, but a reduction of approximately 2.2 log was observed at pH 3.1. Ro145clw is able to withstand pasteurization temperatures (63 and 73 °C), and the thermal stability feature of the phage is likely to be associated with the gene encoding tape measure protein [38]. Son et al found that a STEC O157-specific phage (isolated from bovine intestine) was susceptible to pH changes, with 1 log PFU/mL reductions at either pH 6 or 8 [35].…”
Section: Discussionmentioning
confidence: 99%